Metamorphosis or Metramorphosis? Towards a Feminist Ethics of Difference in Translation - Shread, Carolyn (TTR)

(untitled) (Association canadienne de traductologie, 2007)
AbstractTranslation has been theorized as a process of metamorphosis, either as metaphor (replacing the original) or metonymy (substituting part for original whole). I propose an additional model for translation exchanges: the metramorphic processes described by psychoanalyst Bracha Ettinger. Ettinger expands the scope of interactions by describing maternal/late pre-natal infant relations as ‘subjectivity-as-encounter.’ Her focus on a ‘severality’ preceding autonomous subject positions overcomes the problematic self/other divide and helps us rethink the relation between source and target text. Ettinger posits ‘matrixial’ metramorphosis, which, unlike metamorphosis, does not involve total transformations; rather, it indicates expansion or development. Textually, this means that translations do not efface sources through equivalent matches or inevitable losses, but extend them through exchanges in which sources are still present within translations. An alternative to equivalence as the goal of translation and fidelity as the ethics of translation, a matrixial paradigm reflects the dependency of the source text on the translation, as well as the plurality of many texts prior to translation. A metramorphic translation practice amplifies source texts, mediating them through a less polarized and more interconnected perception of difference which is the grounds for a new feminist ethics.